2020
DOI: 10.1021/acsami.9b22400
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Ozone Sensing Capability of IGZO-Decorated Amorphous Ga2O3 Films

Abstract: In present work, we report a room-temperature ozone sensor using InGaZnO (IGZO)-decorated amorphous Ga2O3 (a-Ga2O3) thin films. The gas sensing tests demonstrate that the topmost IGZO modification can significantly promote the sensors’ responsivity. Intriguingly, the sensing capability presents a first increasing and then decreasing tendency as the surface morphology of IGZO develops from dispersed particles to a continuous film. Finite difference time domain (FDTD) simulation results prove that IGZO nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Recently, some another methods are also being developed to detect the O 3 gas which includes: photoacoustic [293][294][295][296], optical O 3 gas sensors [297][298][299] O 3 gas sensors. Keeratirawee et al [293] reported photoacoustic detection of O 3 gas with a red laser diode using the absorption band.…”
Section: Metal Oxide Semiconductor-based Ozone Gas Sensorsmentioning
confidence: 99%
“…Recently, some another methods are also being developed to detect the O 3 gas which includes: photoacoustic [293][294][295][296], optical O 3 gas sensors [297][298][299] O 3 gas sensors. Keeratirawee et al [293] reported photoacoustic detection of O 3 gas with a red laser diode using the absorption band.…”
Section: Metal Oxide Semiconductor-based Ozone Gas Sensorsmentioning
confidence: 99%
“…The most common materials as sensing materials for impedimetric ozone gas sensors are zinc oxide, indium oxide, tungsten trioxide, and carbon nanotubes. For the sensing layer morphology, different nanostructures are utilised-such as nanocolumns [43], nanorods [26,45], platelets [46,48], nanothin films [44,59,64,[68][69][70], nanoparticles [51,54,58,60,66], nanoislands [52], nanosheets [61], nanotubes [62,63], nanowires [66], and thick films [53]. As substrate, silicon dioxide/silicon, aluminium oxide, glass, aluminium, and quartz and for electrodes platinum, gold, titanium, and copper are commonly employed.…”
Section: Impedimetric Sensorsmentioning
confidence: 99%
“…[14][15][16] It is quite interesting that the performance of UV PD using a-GaO x is comparable or even better than its crystalline counterpart. [15,17] Except for UV PDs, a-GaO x materials also have extensive applications in areas of solar cells, [18][19][20][21] phosphors, [22,23] resistance random access memories (RRAMs), [24][25][26][27] gas sensors, [28] and radiation detectors. [29] These versatile applications together with the fact that scalable a-GaO x can be easily prepared on almost any substrates make it appealing for flexible electronics and giant microelectronics.…”
Section: Introductionmentioning
confidence: 99%